Capacity Building of Village Midwives to Improve Knowledge about Self-Medication at Omben Public Health Center, Sampang Regency, East Java Province - Devy, Shrimarti Rukmini; Pristiany, Liza; Koesbardiati, Toetik (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Pregnancy is a physiological phase that needs to be prepared as well as possible. Sometimes when feeling complaints or symptoms of illness, pregnant women decide to take medication. However, most pregnant women do not know the safe use of drugs during pregnancy. This can certainly affect the health of the mother and the fetus in her womb. Therefore, it is necessary to provide information about self-medication so that pregnant women have sufficient knowledge of the right and safe drug consumption patterns. Based on these problems, this community empowerment program (PKM) is carried out to increase the capacity of village midwives. For this purpose, the study employed a quasi-experimental method. A total of 25 village midwives participated in the research. The program that will be carried out includes providing self-medication materials and communication methods, and training on how to make an RTL (follow-up action plan). After that, village midwives were taught to apply the snakes and ladders media as a means of delivering educational materials to pregnant women. The results of the activity show that there was an increase in the knowledge of village midwives after participating in the community empowerment program, leading to the conclusion that this snakes and ladders media can make it easier for pregnant women to understand the right self-medication during pregnancy so that pregnant women have additional knowledge and benefits in managing themselves regarding the right drug consumption.